{Synthesis and Biological Evaluation of Novel 1′‐Branched and Spironucleoside Analogues} - Chatgilialoglu, Chryssostomos; Ferreri, Carla; Gimisis †, Thanasis; Roberti, Marinella; Balzarini, Jan; De Clercq, Erik (Nucleosides, Nucleotides and Nucleic Acids, 2004)
Novel anomeric spironucleosides and 1′-cyano-2′,3′- didehydro-2′,3′-dideoxyuridine, a structural analogue of known anti-HIV agents, were prepared by nucleophilic addition of organolithium reagents to 1′-cyano-2′-deoxy- and 1′-cyano-2′-deoxy- 2′$β$-bromo-uridine derivatives, respectively. The yield and distribution of products depended on the reaction conditions, which were studied in detail. Although none of the compounds exhibited antiviral activity, two compounds displayed cytostatic activity against both murine leukemia and human T-lymphocyte cells.
Keywords: Cytostatic activity; Nucleophilic addit; [Cyanides